Relationship between oxygen defects and the photocatalytic property of ZnO nanocrystals in Nafion membranes - Wang, Jianchun (Langmuir : the ACS journal of surfaces and colloids, 2009)
ZnO nanocrystals with different oxygen defects (type and concentration) are successfully prepared via the templating method in Nafion membranes. Photoluminescence and infrared characterizations reveal that the concentration of oxygen defects (oxygen vacancy and interstitial oxygen) is quite different for the samples prepared via different synthesis processes. Photocatalytic activity measurements show that the sample with a higher amount of oxygen defects exhibits excellent activity toward the degradation of rhodamine B. Compared with bulk ZnO, ZnO nanocrystals embedded in Nafion membranes have an antiphotocorrosion property. The possible photocatalytic mechanism is discussed in detail, and the oxygen defects are proposed to be the active sites of the ZnO photocatalyst